Digital Literacy in Formal Online Education: A Short Review - Yustika, Gaung Perwira; Iswati, Sri (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This study aims to explain the current findings of digital literacy in formal online education. The methods of research is a type of library descriptionÃ‚Â obtained from relevant scientific articles obtained from internet search media library engines: proquest, researchgate, google scholar and other search engines with keyword search